Cooperative control of air and fuel feeding for PEM fuel cell with ejector-driven recirculation. (25th November 2021) - Yin, Xiaohong; Wang, Xinli; Wang, Lei; Qin, Biao; Liu, Hongbo; Jia, Lei; Cai, Wenjian
Highlights: A model of fuel cell system with ejector-driven recirculation is established. Cooperative control for air and fuel feeding system of fuel cell is proposed. The proposed control strategy has faster response and better chattering rejection. Excess ratios of oxygen and hydrogen and pressure difference are well controlled. Abstract: Air and hydrogen feeding control is a hot topic for the operation of proton exchange membrane (PEM) fuel cell system. However, there is little consideration for the cooperative control of the oxygen excess ratio, hydrogen excess ratio and the pressure balance between anode and cathode. This paper proposed an adaptive super-twisting (ASTW) based sliding mode nonlinear control to regulate air, hydrogen feeding, and pressure balance of PEM fuel cell system with ejector-driven recirculation. The target is to control the oxygen excess ratio, hydrogen excess ratio and the pressure difference on both sides of the membrane, to avoid the oxygen starvation and damage of the membrane. First, a nonlinear model of PEM fuel cell system with ejector-driven recirculation is developed, including fuel cells, ejector and auxiliary equipment. Then, an ASTW based sliding mode control is proposed to achieve the smoothing regulating actions and chattering rejection. The performance of the developed ASTW based sliding mode control strategy is verified through two simulation scenarios and compared with the conventional PID method and STW sliding mode control. Simulation results indicate that the developed control strategy can provide shorter regulation time (less than 5 s) and smaller overshoot (2.1 × 10 4 Pa) of oxygen excess ratio, hydrogen excess ratio and pressure difference on both sides of the membrane than conventional PID controller. Moreover, better chattering rejection can be achieved during various load conditions compared with STW sliding mode control.